2017
DOI: 10.58843/ornneo.v28i0.125
|View full text |Cite
|
Sign up to set email alerts
|

Bird Communities Along Urbanization Gradients: A Comparative Analysis Among Three Neotropical Cities

Abstract: ∙ Urbanization is expanding continuously over rural and natural areas and it is imperative to analyze its effect on bird communities. Although the impact of urbanization on bird communities in the Neotropical region has been explored by several authors, there is a scarcity of comparative studies with standardized methodologies that allow establishing whether the effects of urbanization are similar in different ecoregions. We analyzed the urbanization impact on bird communities in three Neotropical cities. Citi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
0
13
1
8
Order By: Relevance
“…These linear declines arise regardless of if surveys are conducted at randomized locations, or near the center of the largest patch of woodland habitat within each grid cell. Such linear species richness-urbanization intensity patterns have been documented in the relatively small number of similar studies conducted in urban regions, although not all have formally tested for alternative patterns (Chamberlain et al, 2017;Filloy et al, 2019;Leveau et al, 2017;Reis et al, 2012). While our sampling gradient did not extend into natural habitats (i.e., Khao Yai National Park, $100 km from Bangkok center), doing so is unlikely to generate a unimodal richness-urban intensity gradient due to the extremely high avian richness of this location (Round et al, 2011).…”
Section: The Form Of Tropical Species Richnessurbanization Intensity ...mentioning
confidence: 93%
See 1 more Smart Citation
“…These linear declines arise regardless of if surveys are conducted at randomized locations, or near the center of the largest patch of woodland habitat within each grid cell. Such linear species richness-urbanization intensity patterns have been documented in the relatively small number of similar studies conducted in urban regions, although not all have formally tested for alternative patterns (Chamberlain et al, 2017;Filloy et al, 2019;Leveau et al, 2017;Reis et al, 2012). While our sampling gradient did not extend into natural habitats (i.e., Khao Yai National Park, $100 km from Bangkok center), doing so is unlikely to generate a unimodal richness-urban intensity gradient due to the extremely high avian richness of this location (Round et al, 2011).…”
Section: The Form Of Tropical Species Richnessurbanization Intensity ...mentioning
confidence: 93%
“…Such patterns are usually attributed to greater habitat diversity in suburban locations that promote local species richness, even though some specialists are excluded from such locations (Blair & Johnson, 2008;McKinney, 2002;Tratalos et al, 2007). In contrast, in tropical regions avian species richness may decline in a linear manner along urbanization gradients (Bhatt & Joshi, 2011;Leveau et al, 2017;Reis et al, 2012), but hump-shaped patterns have also been reported (Leveau, 2019) and more studies from tropical regions are required (Marzluff, 2001(Marzluff, , 2017. The mechanisms generating linear declines in species richness in tropical regions (Chamberlain et al, 2017;Leveau et al, 2017;Reis et al, 2012), rather than hump-shaped curves, are unclear but may be due to differences in urban form and landscape characteristics with less urbanized locations in tropical regions containing more seminatural habitat and less intensively managed agricultural land compared with those in temperate regions.…”
Section: Introductionmentioning
confidence: 99%
“…Of these species, the t u I and silvereye are native to New Zealand, and the house sparrow was introduced in the mid-1800s (Thomson, 2011). T u I are primarily nectivorous (Bergquist, 1987); silvereyes are primarily insectivorous but also consume large amounts of nectar (Barnett & Briskie, 2007); house sparrows are granivorous, but will opportunistically consume nectar, especially in urbanized areas (Leveau, 2008).…”
Section: Natural History and Study Systemmentioning
confidence: 99%
“…Sin embargo, en particular algunas especies de aves granívoras han sido foco de estudios en los agroecosistemas del centro de Argentina, principalmente en la Región del Espinal, como consecuencia de los conflictos que generan dichas especies sobre las actividades agropecuarias (Murton et al 1974, Bruggers et al 1998, Canavelli et al 2014. Por su parte, los trabajos llevados a cabo hasta el momento con aves granívoras en la Región Pampeana han sido a escala de paisaje y no han considerado la variabilidad estacional (Leveau & Leveau 2004, Weyland et al 2014.…”
Section: Objetivo De La Tesisunclassified